Green materials for sustainable water remediation and treatment - Mishra, Anuradha; Clark, James H. (Cambridge : Royal Society of Chemistry, 2013)
Inadequate access to clean water afflicts people throughout the world, and in developing countries any solution to this challenge must be achieved at a low cost and low energy demand. At the same time, the use of chemicals, and subsequent environmental impact must also be reduced. Green and sustainable water remediation is a rapidly growing field of interest to governments and corporations alike, with considerable input from academics, environmental consultants and public interest groups.This book presents a focused set of articles covering a range of topics in the field, examining not only the adoption of natural products for water remediation, but also the synthesis of new materials and emerging clean technologies. Contributors from across the globe (including some'on the ground' in the developing world) present a comprehensive digest in the form of review-style articles highlighting the current thinking and direction in the field.Interested stakeholders from all sectors will find this book invaluable, and postgraduate students of chemical engineering or environmental science will benefit from the real-world applications presented.
Keywords: Water-supply engineering -- Environmental aspects; Green technology